Prevalence of HIV, Hepatitis B and Syphilis Among Pregnant Women: A Comprehensive Study - Lelya Puput Novita Sari; Winarsih Nur Ambarwati (Jurnal Keperawatan Profesional, 2026)
Sexually transmitted infections (STIs) in pregnant women, especially HIV, Hepatitis B, and syphilis, are a strategic public health issue because they increase the risk of vertical transmission. As part of the national plan for maternal and child health, the Indonesian government is implementing the Triple Elimination Program to stop mother-to-child transmission. However, the widespread lack of local data still poses a barrier to assessing program success at the regional level. The purpose of this study is to provide an overview of the prevalence of PMS in pregnant women in Sukoharjo Regency and to help evaluate how the Triple Elimination program is implemented at the community health center level. This study uses a descriptive observational design with total sampling of all pregnant women undergoing STI screening from January to December 2024. Data were analyzed descriptively using frequency and percentage statistics. Consistent with national trends, the research findings indicate that Hepatitis B is more common than HIV and Syphilis. The results show that strengthening prenatal screening, increasing public awareness, and improving healthcare worker capacity are very important. This study is unique because it provides empirical evidence based on local data. This helps expand the literature and build maternal health policies at the local level.